The structural integrity exerted by N-terminal pyroglutamate is crucial for the cytotoxicity of frog ribonuclease from Rana pipiens - Liao, You-Di (Oxford University Press, 2003)
Onconase, a cytotoxic ribonuclease from Rana pipiens, possesses pyroglutamate (Pyr) at the N-terminus and has a substrate preference for uridine–guanine (UG). To identify residues responsible for onconase’s cytotoxicity, we cloned the rpr gene from genomic DNA and expressed it in Escherichia coli BL21(DE3). The recombinant onconase with Met at the N-terminus had reduced thermostability, catalytic activity and antigenicity. Therefore, we developed two methods to produce onconase without Met. One relied on the endogeneous E.coli methionine aminopeptidase and the other relied on the cleavage of a pelB signal peptide. The Pyr1 substitutional variants maintained similar secondary structures to wild-type onconase, but with less thermostability and specific catalytic activity for the innate substrate UG. However, the non-specific catalytic activity for total RNAs varied depending on the relaxation of base specificity. Pyr1 promoted the structural integrity by forming a hydrogen bond network through Lys9 in α1 and Val96 in β6, and participated in catalytic activity by hydrogen bonds to Lys9 and P(1) catalytic phosphate. Residues Thr35 and Asp67 determined B(1) base specificity, and Glu91 determined B(2) base specificity. The cytotoxicity of onconase is largely determined by structural integrity and specific catalytic activity for UG through Pyr1, rather than non-specific activity for total RNAs.